LPIC-2 Linux Engineer (201-450) - Pezet, Don; Memos, Zachary (Packt Publishing, 2024)
The course begins by laying a solid foundation with an overview of capacity planning, ensuring you understand how to measure and optimize system resources effectively. It then dives into the technicalities of monitoring CPU, memory, disk, and network activity, crucial for maintaining system health and performance. The course focuses on deepening your understanding of Linux's core, including kernel components, modules, and the intricacies of compiling a kernel. You'll learn how to monitor and manage the kernel for peak efficiency, alongside exploring systemd and SysV init systems for better process management. Additionally, system recovery techniques, fstab configuration, and managing swap partitions are thoroughly covered to ensure system resilience. The course wraps up with practical skills in managing storage solutions, network configurations, and troubleshooting, alongside essential system administration tasks such as installing programs from source and effective backup strategies.
Online resource; title from title details screen (O'Reilly, viewed March 20, 2024)
Keywords: Linux -- Study guides -- Examinations; Operating systems (Computers) -- Study guides -- Examinations; Computer networks -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Instructional films; Nonfiction films; Internet videos